Efficacy and tolerability of minocycline in depressive patients with or without treatment-resistant: a meta-analysis of randomized controlled trials - Qiu, Youjia; Duan, Aojie; Yin, Ziqian; Xie, Minjia; Chen, Zhouqing; Sun, Xiaoou; Wang, Zhong; Zhang, Xuwei (Frontiers in Psychiatry, 2023)
Background: Minocycline, an antibiotic with anti-inflammatory, antioxidant, and neuroprotective properties, has been used for treating psychiatric disorders in research. This systematic review aimed to evaluate the efficacy and tolerability of minocycline in patients having depression with or without treatment-resistance. Methods: Electronic databases including Embase, PubMed, and the Cochrane library were searched for relevant studies published up to October 17, 2022. The primary efficacy outcome was the change in depression severity scores and the secondary efficacy outcomes included the changes in Clinical Global Impression (CGI) and Beck Depression Inventory (BDI) scores and the incidence of response and partial response. Safety outcomes were evaluated based on the incidence of classified adverse events and all-cause discontinuation. Results: Five studies with 374 patients were selected for analysis. The minocycline group demonstrated a significant reduction in depression severity scale (standardized mean difference [SMD]: -0.59, 95% confidence interval [CI]: -0.98 to -0.20, P=0.003) and CGI (SMD: -0.28, 95% CI: -0.56 to -0.01, P=0.042) scores; however, no statistical difference was found in terms of the BDI score, response, and partial response. No significant differences were found between the groups in terms of adverse events (other than dizziness) and discontinuation rates. Subgroup analysis showed that minocycline was also effective in reducing depression severity scores in treatment-resistant depression (SMD: -0.36, 95% CI: -0.64 to -0.09, P=0.010). Subgroup analysis of Hamilton Depression Rating Scale (17-item) scores showed a statistical difference in response in patients with depression (relative risk: 2.51, 95% CI: 1.13 to 5.57, P=0.024). Conclusions: Minocycline may improve depressive symptoms and augment response to treatment in patients with depression irrespective of treatment-resistance. However, clinical trials with large sample sizes are warranted for evaluating long-term outcomes with minocycline.